The pedagogy of hope at IMSTUS: Interpretation and manifestation - Ndlovu , MC (South African Journal of Higher Education, 2011)
The purpose of this chapter is to discuss how the idea of a Pedagogy of Hope is perceived, interpreted and realised at the Institute for Mathematics and Science Teaching of the University of Stellenbosch (IMSTUS). First some background information is given about the impact of the programmes which, it is argued, cannot be pinned to one Millennium Development Goal (MDG) theme. The focus then shifts to how IMSTUS adopts a pragmatic rather than theoretical interpretation of the University’s vision of a pedagogy of hope by engaging in reflection-in-action to bring about redress in mathematics and science education to historically disadvantaged learners. It is concluded that the impact of the innovative interventions at the Institute turns despair into hope for learners who would otherwise have had no opportunity to realize their hopes and dreams in participating fully, as democratic citizens, in the socio-economic development of the country.